OVERCOMING CHALLENGES IN VIRTUAL CLASSROOM TO MAINTAIN EFFECTIVE CLASSROOM MANAGEMENT AND CLASSROOM CULTURE: A CASE STUDY AT ONE VOCATIONAL SCHOOL - Ridha Mardiani; Ridha Nurul Azhar (Lembaga Penelitian Universitas Pasundan, 2021)
Effective classroom management supports the teacher classroom teaching profoundly. During Pandemic COVID 19 most classroom teachings are conducted in virtual classroom that have been greatly affected the way how teacher manage his or her own classroom. This causes some challenges for teachers in managing his or her virtual classroom. This study was conducted in the form of a case study in one vocational school in West Bandung region, West Java, Indonesia in which one English teacher was purposively selected as the participant of the research and one class consisted of 27 students. The objectives of this study are: (1) to find out the challenges of teacher in classroom management in virtual classroom (2) to find out what classroom management the teacher used in her virtual classroom. The researchers employed a qualitative case study which used classroom observation and teacher interview as main instrument. Data from classroom observation and interview transcript were analyzed according to the themes, coding and categorizing to answer the research questions. The results indicate that the teacher experienced many challenges in the virtual classroom, such as the students’ unreadiness to join the virtual class, internet connection problem, restricted time so that the teacher immediately taught the core material, students turned off the camera and sound, students learnt unattentively, less interaction and inappropriate class control. Some suggestions are given to the challenges occurred in their virtual classroom such as, by a) joining the virtual classroom earlier; b) checking the students’ attendance first; c) optimizing the teacher-students interaction during whilst- learning and post learning activity; and d) giving quizzes at the end of the lesson to make the students are more enthusiastic in learning. In this study, it is found that the teacher employed a combination of democratic and leisurely classroom management style. This finding leads to the point where a new style for virtual classroom management called Maye’s Conceptualization Model is proposed.